Analisis Makna Konotatif dalam Terjemahan Lagu-Lagu Indila dari Bahasa Prancis kedalam Bahasa Indonesia - Marsyanda Ratu Ayu Alya Ramadhan; Yuliarti Mutiarsih; Farida Amalia (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This study discusses the analysis of connotative meaning in the translation of Indila’s song lyrics from Frenc to Bahasa Indonesia. Connotative meaning plays an important role in conveying emotional and aesthetic messages. The aim of this research is to identify the forms of connotative meaning in the translated lyrics and to classify them based on Peter Newmark’s translation methods. This study employs a descriptive qualitative approach with purposive sampling on three songs by Indila from the Mini World (2014) album: Dernière Danse, Tourner Dans Le Vide, and Love Story. The results show that connotative meaning plays a crucial role in expressing emotional messages in there songs. A total of 51 lines containing connotative meaning were found, with the dominant translation methods being the idiomatic translation (25 data), semantic translation (19), and communicative translation (5 data).